2018
DOI: 10.1590/18069657rbcs20170251
|View full text |Cite
|
Sign up to set email alerts
|

Daycent Simulation of Methane Emissions, Grain Yield, and Soil Organic Carbon in a Subtropical Paddy Rice System

Abstract: ABSTRACT:The DayCent ecosystem model, widely tested in upland agroecosystems, was recently updated to simulate waterlogged soils. We evaluated the new version in a paddy rice experiment in Southern Brazil. DayCent was used to simulate rice yield, soil organic carbon (SOC), and soil CH 4 fluxes. Model calibration was conducted with a multiple-year dataset from the conventional tillage treatment, followed by a validation phase with data from the no-tillage treatment. Model performance was assessed with statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…The Eh in soil changes based on the flooded or drainage conditions. Continuous flooding, whether by rainfall, irrigation or both, would be a FLOD 2 period in the model schedule, with maximum Eh of -250 mV (Cheng et al, 2013, Weiler et al, 2018. The water conditions under rainfall do not saturate in the model, therefore fixed values (-20 mV) were indicated as FLOD 1.…”
Section: Mitigation Scenarios and Net Ghg Balancementioning
confidence: 99%
See 2 more Smart Citations
“…The Eh in soil changes based on the flooded or drainage conditions. Continuous flooding, whether by rainfall, irrigation or both, would be a FLOD 2 period in the model schedule, with maximum Eh of -250 mV (Cheng et al, 2013, Weiler et al, 2018. The water conditions under rainfall do not saturate in the model, therefore fixed values (-20 mV) were indicated as FLOD 1.…”
Section: Mitigation Scenarios and Net Ghg Balancementioning
confidence: 99%
“…Eh approximations are specific to the methane model. Further development of the Eh algorithm was suggested by Weiler et al, (2018), where they found contrasting results between simulated and observed CH4 emissions in flood-irrigated rice paddy fields under no tillage in southern Brazil. Soil water and gas filled pore space in the current version are normal inputs to the N2O emissions, but are not currently considered in the methane Eh equations.…”
Section: Mitigation Scenarios and Net Ghg Balancementioning
confidence: 99%
See 1 more Smart Citation
“…This finding is in accordance with other studies conducted with the DayCent model under different agricultural management systems (Del Grosso et al, 2001;Del Grosso et al, 2008;Smith et al, 2012;Begum et al, 2018;Weiler et al, 2019). As was also observed by Oliveira et al (2017) and Weiler et al (2018), the model modified in this study overestimated the soil C and N stocks. However, this result is considered acceptable considering the complexity of the management systems evaluated in these studies.…”
Section: Model Simulation Efficiencysupporting
confidence: 93%
“…For the four paddocks independently evaluated, the behavior of aboveground biomass shows that even with some differences, it was still possible to represent the ICLS (Figure 9). The model did not overestimate or underestimate aboveground biomass for the study period; previous studies have reported a DayCent tendency to underestimate grain yield and aboveground biomass [11,78,79]. Generally, significant errors may occur because the model does not consider several processes that depend on crop management, such as those associated with biotic stresses from weeds, diseases, or insects [80].…”
Section: Validated Modelmentioning
confidence: 83%